A compact broadband differential‐fed microstrip patch antenna with 5.8 GHz WLAN band‐notched under quad‐mode resonance. Issue 4 (27th December 2019) - Feng, Shu; Zhang, Li; Weng, Zi‐Bin; Jiao, Yong‐Chang
Abstract: A compact broadband differential‐fed microstrip patch antenna with 5.8 GHz WLAN band‐notched under quad‐mode resonance is proposed in this article. The antenna consists of two hybrid shape radiation patches and a pair of capacitances loaded loop (CLL) resonators. The broadband performance is achieved by integrating TM10 and TM01 radiation modes of rectangular patches and TM1, 0, −1 radiation mode of triangular patches. Then these three radiation modes are adjusted close to each other to form a wide operation band. After that, with the loading of CLL resonators, a nonradiative resonant mode is introduced. Thus, the low‐frequency band of the proposed antenna can be further expanded, and a frequency notch point is introduced in 5.8 GHz WLAN band. Finally, the proposed antenna is fabricated and measured. The measured impedance bandwidth is about 43.5% (5.93‐9.23 GHz) while keeping a compact structure without any air gaps. Additionally, the broadside gain is varied from 4 to 6 dBi with a notch point at 5.8 GHz.